Clinical study of the relationship between hepatitis B core antibody and mechanical ventilation in patients with Guillain-Barré syndrome - Zhang, Wei; Yao, Qian; Wang, Yuqiao; Yin, Junxiong; Yang, Xinxin (Frontiers in Neurology, 2025)
IntroductionThe aim of this study was to investigate the association between hepatitis B core antibody (HBcAb) positivity and the need of mechanical ventilation (MV) in patients with Guillain-Barré syndrome (GBS).MethodsWe retrospectively analyzed the clinical data of 159 patients who were diagnosed with GBS between December 2014 and April 2023 in the Affiliated Hospital of Xuzhou Medical University. Patients were categorized into two groups according to the need for MV. Variables that were significantly different between the two groups in univariate analysis were analyzed through multivariate logistic regression models.ResultsThe final study population included 159 patients, 28 (17.6%) of whom need MV. In univariate analysis, Medical Research council sum score (MRC) on admission (p < 0.001), bulbar paralysis (p < 0.001), autonomic dysfunction (p < 0.001), HBcAb (p = 0.009), neutrophil/lymphocyte ratio (NLR) (p < 0.001), and Serum albumin (p = 0.016) were associated with MV. Multivariate logistic regression analysis showed lower MRC on admission (OR = 0.946, 95%CI: 0.908–0.985, p = 0.008), bulbar paralysis (OR = 3.726, 95%CI: 1.118–12.421, p = 0.032), autonomic dysfunction (OR = 3.804, 95%CI: 1.058–13.679, p = 0.041), HBcAb positivity (OR = 6.154, 95%CI: 1.253–30.229, p = 0.025), and higher NLR (OR = 1.214, 95%CI: 1.039–1.417, p = 0.014) were the risk factors for the need of MV in patients with GBS.ConclusionHBcAb positivity increased the risk of MV in patients with GBS. Lower MRC on admission, bulbar paralysis, autonomic dysfunction, and higher NLR were the risk factors for the need for MV.